Hukuman Bagi Pelaku Seks Komersial - Eriyani Mendrofa; Sumiyati Sumiyati (Integritas: Jurnal Teologi, 2020)
The issue of punishment for commercial sex offenders continues to be debated both in social, psychological, and legal aspects. Through this paper, the author presents a conceptual analysis related to the issue. For the writer, the punishment for commercial sex workers is not right. The author proposes a more human approach to refer to Jesus' actions. This coaching is expected to be more inclined to positive personal recovery from a woman or man who is a former commercial sex offender.